First contact: the role of respiratory cilia in host-pathogen interactions in the airways - Kuek, Li Eon; Lee, Robert J. (American journal of physiology. Lung cellular and molecular physiology, 2020)
Respiratory cilia are the driving force of the mucociliary escalator, working in conjunction with secreted airway mucus to clear inhaled debris and pathogens from the conducting airways. Respiratory cilia are also one of the first contact points between host and inhaled pathogens. Impaired ciliary function is a common pathological feature in patients with chronic airway diseases, increasing susceptibility to respiratory infections. Common respiratory pathogens, including viruses, bacteria, and fungi, have been shown to target cilia and/or ciliated airway epithelial cells, resulting in a disruption of mucociliary clearance that may facilitate host infection. Despite being an integral component of airway innate immunity, the role of respiratory cilia and their clinical significance during airway infections are still poorly understood. This review examines the expression, structure, and function of respiratory cilia during pathogenic infection of the airways. This review also discusses specific known points of interaction of bacteria, fungi, and viruses with respiratory cilia function. The emerging biological functions of motile cilia relating to intracellular signaling and their potential immunoregulatory roles during infection will also be discussed.